ANALISIS PENGARUH KECUKUPAN MODAL, EFISIENSI OPERASIONAL DAN LIKUIDITAS TERHADAP PROFITABILITAS BANK BUMN DI BURSA EFEK INDONESIA PERIODE 2009-2013 - Ayik Muh. Al Hasny; Christin Berlinhan Oey (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2016)
This study aims to examine the effect of the variables of Capital Adequacy Ratio (CAR), operational efficiency (ratio of operating expenses to operating income / BOPO) and liquidity (loan to deposit ratio / LDR) to profitability (return on assets / ROA)of state-owned bank in the Indonesia Stock Exchange in the period of 2009 -2013. There are four (4) samples in this research, which are: PT Bank Mandiri Tbk., PT Bank Rakyat Indonesia Tbk., PT Bank Negara Indonesia Tbk, and PT Bank BTN Tbk. Data analysis method used is multiple linear regression, after going through the classical assumption test to make sure there are no violations on multicolinearity, autocorrelation and heteroscedasticity. Based on the analysis, it is concluded that the variables CAR, BOPO and LDR, partially or simultaneously, significantly influences ROA of the state-owned bank in BEI. Of the three variables, it is proven that BOPO is the most dominant aspect that influences ROA. The coefficient of determination (R2) is of 0.795, means that the three variables have contributed to changes in the value of ROA of 79.5% and the contribution of other variables that are not observed in this study is 20.5%. While the value stimulant correlation coefficient (R) is 0.891 indicates that these three variables have a strong relation to the ROA of state-owned bank in BEI 2009-2013.